2022
DOI: 10.3390/pharmaceutics15010151
|View full text |Cite
|
Sign up to set email alerts
|

Aptamers Enhance Oncolytic Viruses’ Antitumor Efficacy

Abstract: Oncolytic viruses are highly promising for cancer treatment because they target and lyse tumor cells. These genetically engineered vectors introduce therapeutic or immunostimulatory genes into the tumor. However, viral therapy is not always safe and effective. Several problems are related to oncolytic viruses’ targeted delivery to the tumor and immune system neutralization in the bloodstream. Cryoprotection and preventing viral particles from aggregating during storage are other critical issues. Aptamers, shor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 108 publications
0
4
0
Order By: Relevance
“…To increase the stability of the aptamer, it is either modified or conjugated with various composite structures (liposomes, dendrimers, nanoparticles, etc.) [ 26 ]. However, when using them in situ, this time is quite sufficient for diagnosing tumor cells [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To increase the stability of the aptamer, it is either modified or conjugated with various composite structures (liposomes, dendrimers, nanoparticles, etc.) [ 26 ]. However, when using them in situ, this time is quite sufficient for diagnosing tumor cells [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…To overcome this problem, it may be useful to either evaluate the remaining truncated aptamers for immunoshielding [ 21 ] or perform a SELEX procedure on this particular virus strain, VV-GMCSF-Lact. Additionally, to overcome this issue, one of the possible solutions is to enhance the virus targeting by using a bifunctional aptamer that can bind both to the virus and to neutralizing antibodies [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Oncolytic viruses (OV) are a new class of drugs that have the ability to selectively replicate in tumor cells and lyse targets through a variety of mechanisms, including cytotoxic cytokine directed oncolytic, tumor vascular targeting, and bystander effects [ 67 , 68 ]. OV has a recognized application in cancer immunotherapy [ 69 73 ]. As an ideal vector, OV can be payload specific delivered into the tumor environment after administration [ 74 ].…”
Section: The Involvement Of Cd47 In Ovarian Cancer Immunotherapymentioning
confidence: 99%
“… 15 Nucleic acid aptamers (Apts) are short oligonucleotide fragments, including single-stranded DNA or small molecule RNA, which have shown great potential for targeted diagnosis and treatment of tumors. 16 , 17 Compared with traditional antibodies, Apts have numerous advantages, such as easy screening and synthesis, lower molecular weight, high stability, low immunogenicity, and rapid blood clearance. 18 20 A recent study showed that a single-stranded DNA aptamer called S2.2 (5′-GCAGTTGATCCTTTGGATACCCTGG-3′) could specifically bind to MUC1 for BC diagnosis and targeted therapy.…”
Section: Introductionmentioning
confidence: 99%